Análise das patologias apresentadas no hospital Santa Casa de Campo Mourão com soluções para o reparo - Silva, Oales Corso da (2018)
The following work was elaborated with the objective of proposing solutions for cases of pathologies existing in the Hospital Santa Casa de Campo Mourão-PR. Because it is a public institution and of great importance to the community, it is, necessary a careful analysis to find a solution that is economically and constructively feasible, so that there is no aggravation of the problems causing a commitment to the progress of the services provided by the hospital. The paper presents a theoretical review on how to identify the pathological symptoms and how to solve them. Identifying the existing pathologies in the building, determine the responsible mechanisms with the purpose of proposing solutions through a report with constructive details, ensuring the preservation of the structure against the action of pathological agents.